(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
The present work was aimed to study the effect of extracted phenolic compounds from Salicornia air part by several solvents as natural antioxidants on preservation of corn oil comparing with synthetic antioxidant (TBA) on the oil stability against oxidative rancidity during storage at 70 °C for 5 days. The results indicate that the best solvent for extracting polyphenolic compounds was methanol followed by ethanol, chloroform and water. HPLC analysis for the total polyphenols extracted from the air part of salicornia fruticosa indicated to presence high percentages of Pyrogallol, Ellagic, B-OH Benzoic and Catechin. The extracted phenolic acids were tested against corn oil keeping quality. Results show that peroxide value and TBA values of corn oil that treated by different types of extracts at different levels were lower than control. Keywords: Salicornia fruticosa; DPPH; Corn oil; Phenolic extract. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18856 Bangladesh J. Sci. Ind. Res. 49(1), 53-58, 2014